Creating Shared Values through Human Resource Activities: Toward an Effective Transformation Programme - Hasnan, Norlena (Journal of Business Management and Accounting, 2015)
Numerous literature works emphasised on shared values and the role it plays in the organisation. The value and system form the basis of a strong culture that enables the organisation to better react to any transformation plan. As with most of the public organisations in Malaysia, the government has set up the Government Transformation Programme (GTP), an ambitious, broad-based programme of change to fundamentally transform the government organisation into an efficient and citizen-centred institution. Hence,all Malaysian government organisations need to work fast and smart in order to realise the objectives of Vision 2020. The shared values concept is considered as the prerequisite to shape the standards and expectations held by employees of these organisations that help to guide aspects of practice performance. Generally in services, the core values of support, respect of choice, collaboration, and customer service form the basic foundation of a trusting therapeutic relationship. Hence, this paper presents acase of a government agency which is in the process of implementing a transformation plan. Before the department can move forward with the transformation agenda, it is critical to understand the current values and practices, which would subsequently enable to identify the values that can be formed through human resource activities. The case provides valuable insight into the necessary parts of the transformation process, particularly in developing the right values and practices in the government sector.
Keywords: Transformation plan; shared values; human resource activities; government department